Supply Chain-Based Coral Conservation: The Case of Mozuku Seaweed Farming in Onna Village, Okinawa - Omoto, Reiko; Uehara, Masato; Seki, Daigo; Kinjo, Masaru (Sustainability, 2024)
Blue foods, including seaweed, have been overlooked in food systems analysis and policy-making due to a lack of available data. However, seaweed cultivation is gaining attention as a restorative aquaculture that could contribute to ocean health by serving as blue carbon or nurturing seagrass beds. Commercial restorative aquaculture may provide market-based solutions for improving ocean health. The Onna Village Fisheries Cooperative producers have been restoring corals, knowing empirically that when the coral weakens, the yield of Mozuku seaweed drops. Furthermore, measures taken to reduce red soil run-off prevent the reduction in Mozuku quality and quantity and protect seagrass beds, since Mozuku cultivators have continued to use them as an important nursery. The fishery cooperative and the seaweed processing company, Igeta Takeuchi Co., Ltd., have jointly developed high-quality Mozuku that is resistant to climate change and extreme weather conditions through strain selection. Based on this case, this paper examines the following questions: (1) What quality assurance technique is necessary to continue restorative aquaculture as a market-based solution over the long term? (2) What social platforms and communication channels are available to stakeholders to maintain restorative aquaculture in the long run? To answer these questions, Japanese consumer cooperatives that established “the Mozuku Fund” are also examined. This case study of Mozuku highlights how the sustainability and quality of marine products are maintained throughout the whole supply chain, focusing on the power of the Japanese consumers’ cooperative.